1995
DOI: 10.1891/0886-6708.10.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Distress and Symptoms of Posttraumatic Stress Disorder in Abused Women

Abstract: Emotional distress and symptoms of posttraumatic stress disorder (PTSD) were examined among women in psychologically abusive relationships. Women (N = 93) were divided into three groups (none, moderate, severe) according to scores on the violence subscale of the Severity of Violence Against Women Scales (Marshall, 1992). All groups reported serious emotional distress on the Symptom Checklist 90-Revised (Derogatis, 1983) dimensions (e.g., more so than 93% of the nonclinical norm for global distress). Psychotici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
1
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(81 citation statements)
references
References 0 publications
8
69
1
2
Order By: Relevance
“…Indeed, prior research has suggested that IPV has a negative influence on parenting behaviors (DeVoe & Smith, 2002;Levendosky, Lynch, & Graham-Bermann, 2000). Parenting may be impaired because of the stress of experiencing IPV and its resultant negative effects on the mental health of the woman (Astin, Lawrence, & Foy, 1993;Astin, Ogland Hand, Coleman, & Foy, 1995;Vitanza, Vogel, & Marshall, 1995). Exposure to IPV may inhibit a mother's ability to regulate her own affects and behaviors which may compromise her ability to engage in wellregulated interactions with her infant.…”
Section: The Importance Of Context: the Effect Of Ipv On Parentingmentioning
confidence: 99%
“…Indeed, prior research has suggested that IPV has a negative influence on parenting behaviors (DeVoe & Smith, 2002;Levendosky, Lynch, & Graham-Bermann, 2000). Parenting may be impaired because of the stress of experiencing IPV and its resultant negative effects on the mental health of the woman (Astin, Lawrence, & Foy, 1993;Astin, Ogland Hand, Coleman, & Foy, 1995;Vitanza, Vogel, & Marshall, 1995). Exposure to IPV may inhibit a mother's ability to regulate her own affects and behaviors which may compromise her ability to engage in wellregulated interactions with her infant.…”
Section: The Importance Of Context: the Effect Of Ipv On Parentingmentioning
confidence: 99%
“…Third, psychological abuse may precede violence (Hilberman andMunson, 1977-1978;Star, 1982, Stets, 1990 and, therefore, be predictive of a violent incident (FoUingstad, Laughlin et al, 1991). Fourth, psychological abuse has been associated with PTSD (Dickstein, 1988;Vitanza et al, 1995) and serious physical and psychological symptomology (Geffner and Pagelow, 1990;Hoffman, 1984;Marshall, 1993a,b;Tolman and Bhosley, 1991;Vitanza et a/., 1991) including attempted suicide (Stephens, 1985). The variety of sources from which women seek help for psychological abuse is as broad as it is for women experiencing physical or sexual aggression (Hamilton and Coates, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…With few exceptions (Laner, 1989a,b;Marshall, 1993a,b;Powers, 1986;Stets, 1991;Vitanza et aL, 1995) researchers have used overt, easily recognizable acts for items (e.g., Hoffman, 1984;Laner, 1985;Renzetti, 1992;Retzinger, 1991;Marshall, 1990, 1991;Stets, 1991;Tolman, 1992) and scales (Hudson and Mclntosh, 1981;Rodenberg and Fantuzzo, 1992;Shephard and Campbell, 1992;Tolman, 1989) measuring psychological abuse. Yet, different men may enact different types (Mills, 1985) or levels of psychological aggression (Saunders, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…This is of concern because domestic violence victims have increased rates of mental health problems, such as depression, anxiety, posttraumatic stress disorder, substance abuse and dependence, and suicidal ideation. [39][40][41][42][43] Intervention enhanced screening on the night shift, as night workers were less likely to screen preintervention, possibly reflecting a generalized decrease in vigilance, mood, and circadian harmony in emergency department shift workers. 44 Shift workers may require targeted interventions, because victims are sometimes overrepresented on the night shift.…”
Section: Discussionmentioning
confidence: 99%